2023
DOI: 10.1101/2023.07.26.550728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivoexpansion of gene-targeted hepatocytes through transient inhibition of an essential gene

Abstract: Homology Directed Repair (HDR)-based genome editing is an approach that could permanently correct a broad range of genetic diseases. However, its utility is limited by inefficient and imprecise DNA repair mechanisms in terminally differentiated tissues. Here, we tested ″Repair Drive″, a novel method for improving targeted gene insertion in the liver by selectively expanding correctly repaired hepatocytesin vivo. Our system consists of transient conditioning of the liver by knocking down an essential gene, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…On the other hand, researchers aiming to target the Alb locus by CRISPR/Cas9-mediated HR discovered secondary off-target genes in Tfr and Afp 44 . More recently, De Giorgi et al, used CRISPR/Cas9-mediated HR to perform genome editing in the hepatic Apoa1 locus and found integrated AAV vectors again in Alb , Afp , and Errfi1 loci 45 . Interestingly, the genes that are prone to off-target AAV integration have high R-loop levels (Fig.5a), although, the most frequent “off-target” gene in the liver is Alb which is also the most highly transcribed locus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, researchers aiming to target the Alb locus by CRISPR/Cas9-mediated HR discovered secondary off-target genes in Tfr and Afp 44 . More recently, De Giorgi et al, used CRISPR/Cas9-mediated HR to perform genome editing in the hepatic Apoa1 locus and found integrated AAV vectors again in Alb , Afp , and Errfi1 loci 45 . Interestingly, the genes that are prone to off-target AAV integration have high R-loop levels (Fig.5a), although, the most frequent “off-target” gene in the liver is Alb which is also the most highly transcribed locus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5) . Of note, the Alb locus was the most common 'off-target' genome region where the vector was found integrated in all the studies taken into consideration [42][43][44][45] . Thus, we speculate that a combination of high transcription (Alb is the highest transcribed gene in liver) and R-loop levels might promote AAV vector genome integration, without ruling out the possibility that this combination of events could also lead to increased DNA damage which in turn could also favor AAV integration 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed complex mis-integration profiles in CRISPR KI experiments at the Cas9 on-target cut-site, including incomplete integration, asymmetric HDR (defined as repair events showing a proper HDR junction at one of the two homology arms, while repair at the other homology arm resolves through a non-HDR mechanism), AAV capture and AAV concatemer capture. 28 , 29 Although primarily maintained in an episomal state, AAV genome can be integrated into the host genome at CRISPR on-target and OT cut-sites. 30 Currently no single tool can detect all the complex integration outcomes, especially events occurring with very low frequencies.…”
Section: Discussionmentioning
confidence: 99%